The Caffeine Analysis in Tea Bag and Robusta Coffee Using UHPLC Methods - Sutomo, Ahmad; Ridwan, Muhammad; Suswidiantoro, Vicko; Pisacha, Iga Mayola; Daskar, Annajim; Rosanti, Afi Sania (PT FORMOSA CENDEKIA GLOBAL, 2024)
Caffeine, a natural psychostimulant, enhances arousal by inhibiting the effects of adenosine on the dopamine pathway. This study aimed to analyze and compare caffeine concentrations in seven robusta coffee samples (coded RC) and five black tea bags (coded BT) using both qualitative and quantitative methods. Qualitative tests employed Dragendorff reagents for coffee and Parry reagents for tea, confirming caffeine presence through colorimetric changes. Quantitative analysis utilized reverse-phase UHPLC, with a mobile phase of aquabidestilata and methanol (60:40), a C18 stationary phase at 40°C, and detection at 272 nm. Validation parameters demonstrated strong performance, with an RSD of 0.573%, a linear correlation coefficient of 0.998 for concentrations between 100–250 ppm, a LoD of 1.02 ppm, a LoQ of 3.10 ppm, and 99.88% accuracy. Results showed robusta coffee sample RC3 contained the highest caffeine concentration at 26.00 mg/serving, while black tea sample BTB3 exhibited 2.44 mg/serving. Despite higher caffeine levels in robusta coffee compared to black tea, both remained below the SNI threshold of 50 mg/serving, confirming their safety for consumption.